Perkecambahan Polen Bunga Jengger Ayam (Celosia argantea) - Nafila Alifia Azka (Agrotechnology Innovation Center, Universitas Gadjah Mada, Yogyakarta, 2021)
Celosia cristata is one of specialty cut flowers category. Celosia cristata has leaf color, leaf shape and stem color diversity. The diversity in Celosia cristata has attracted the attention of breeders to develop new varieties of this commodity by means of hybridization. Therefore, before the hybridization of Celosia cristata is being conducted, it is necessary to study the estimated time required for pollen to reach the embryo sac and fertilization occurs to ensure the probability of successful hybridization in plant breeding program. Pollen germination in this study was carried out by in vitro method using pollen germination media consisting of 12 grams of sucrose, 0.01 grams of H3BO3, 100 ml of distilled water, and 0.1 M HCl or 0.1 M NaOH (to maintain the pH of the media at pH 6.4). The germinated pollen was observed with a microscope until the germination reed reached its maximum length, then the length of the germination reed was measured. The measured growth of germination reeds was then compared with the length of the distance from the stigma to the embryo sac. After that, the estimated time required from pollination to fertilization was being predicted. Based on the results of the study, the estimated time needed by Celosia cristata from pollination (pollen fall to the stigma) to fertilization (fusion between male and female gamete cells) was 131.9 minutes.